Peningkatan Keterampilan Berbicara Siswa Menggunakan Metode Role Playing pada Pembelajaran Bahasa Indonesia di Kelas IV SDN 2 Cibanteng - Rosmawati, Euis; Chandra, Deni; Dwi Febriani, Winarti (Indo-MathEdu Intellectuals Journal, 2024)
This study aims to improve students' speaking skills through the implementation of the role-playing method in Indonesian language learning. The research method used is classroom action research (CAR), which consists of planning, action, observation, and reflection in each cycle. The subjects of this study are 32 students, consisting of 17 female and 15 male students. Based on the research results, the students' speaking skills are still low; students tend to be shy, less expressive, hesitant, and confused about what to say. Students have not mastered linguistic factors such as pronunciation accuracy, intonation, and word choice. The role-playing learning method involves students extensively in speaking through drama activities. The results of this study indicate that students' speaking skills improved using the role-playing method. In the first cycle, the average score was 76.6, with 23 students passing and 9 students not passing, resulting in a percentage of 71.88% categorized as high. There was an improvement in the second cycle, with an average score of 87.96, where 30 students passed and 2 students did not, resulting in a percentage of 93.75% categorized as very high